Analisis Implementasi dan Keberlanjutan Bisnis Pizzato di Kota Palembang - Hansen Wijaya; Megawati S.E., M.Si (Universitas Multi Data Palembang, 2026)
This study aims to examine the implementation and sustainability of Pizzato as an innovation-driven culinary food business. Pizzato is a culinary enterprise that develops pizza products using potatoes as the primary ingredient, representing a form of product diversification and differentiation from conventional pizza products that are predominantly made from wheat flour. The business offers three menu variants as part of its product development strategy to accommodate diverse consumer preferences. The scope of analysis in this study encompasses an evaluation of the marketing mix strategy, an assessment of business performance as reflected in financial statements, and an analysis of business sustainability. The findings indicate that the Pizzato business is feasible to implement and demonstrates potential business sustainability through the application of effective marketing strategies and sound financial management.